Konsep Partisipasi Publik dalam Perancangan Rancanga Undang-Undang Kitab Undang-Undang Hukum Acara Pidana - Ailsa Cahya Dewi; Raissa Aulia Zahra; Alini Adelia Arjeni; Auckland Amozaic; M. Akbar Rizky Pratama (VJJ, 2023)
As a state of law that upholds popular sovereignty, Indonesia mandates meaningful public participation, consistent with the Constitution and Constitutional Court Decision No. 91/PUU-XVIII/2020, which guarantees the right of citizens to be heard, to have their considerations taken into account, and to be explained. However, the hastily enacted Criminal Procedure Code Bill (RUU KUHAP) has faced widespread critism due to a lack of transparency and a discernible tendency toward expanding the authority of law enforcement officials without adequate judicial oversight. This expansion risks violating the constitutional rights of citizens and fundamentally deviates from the principile of due process of law. Therefore, this journal aims to criticaly analyze the participation deficit and the normative deviations observed in the drfting of the RUU KUHAP, with the ultimate goal of advocating for a more just and democratic criminal procedure system. Keywords: Partisipasi Masyarakat; Meaning Participation; RUU KUHAP; Perancangan Perundang- undangan